Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the quadratic equation [tex]\(5x^2 + 3x - 4 = 0\)[/tex] using the quadratic formula, we follow these steps:
1. Identify the coefficients: For the given quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex], the coefficients are:
- [tex]\(a = 5\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = -4\)[/tex]
2. Quadratic Formula: The quadratic formula is given by:
[tex]\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}} \][/tex]
3. Substitute the coefficients into the formula:
- [tex]\(a = 5\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = -4\)[/tex]
Substituting these values into the quadratic formula, we get:
[tex]\[ x = \frac{{-3 \pm \sqrt{{3^2 - 4 \cdot 5 \cdot (-4)}}}}{{2 \cdot 5}} \][/tex]
4. Simplify inside the square root:
- Calculate the discriminant [tex]\(b^2 - 4ac\)[/tex]:
[tex]\[ 3^2 - 4 \cdot 5 \cdot (-4) = 9 + 80 = 89 \][/tex]
5. Write out the final solution:
[tex]\[ x = \frac{{-3 \pm \sqrt{89}}}{{10}} \][/tex]
Based on these steps, the correct form is:
[tex]\[ x = \frac{-3 \pm \sqrt{(3)^2 - 4(5)(-4)}}{2(5)} \][/tex]
Thus, the correct equation that shows the quadratic formula used correctly is:
[tex]\[ x = \frac{-3 \pm \sqrt{(3)^2 - 4(5)(-4)}}{2(5)} \][/tex]
1. Identify the coefficients: For the given quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex], the coefficients are:
- [tex]\(a = 5\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = -4\)[/tex]
2. Quadratic Formula: The quadratic formula is given by:
[tex]\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}} \][/tex]
3. Substitute the coefficients into the formula:
- [tex]\(a = 5\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = -4\)[/tex]
Substituting these values into the quadratic formula, we get:
[tex]\[ x = \frac{{-3 \pm \sqrt{{3^2 - 4 \cdot 5 \cdot (-4)}}}}{{2 \cdot 5}} \][/tex]
4. Simplify inside the square root:
- Calculate the discriminant [tex]\(b^2 - 4ac\)[/tex]:
[tex]\[ 3^2 - 4 \cdot 5 \cdot (-4) = 9 + 80 = 89 \][/tex]
5. Write out the final solution:
[tex]\[ x = \frac{{-3 \pm \sqrt{89}}}{{10}} \][/tex]
Based on these steps, the correct form is:
[tex]\[ x = \frac{-3 \pm \sqrt{(3)^2 - 4(5)(-4)}}{2(5)} \][/tex]
Thus, the correct equation that shows the quadratic formula used correctly is:
[tex]\[ x = \frac{-3 \pm \sqrt{(3)^2 - 4(5)(-4)}}{2(5)} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.